2021
DOI: 10.3174/ajnr.a7010
|View full text |Cite
|
Sign up to set email alerts
|

Ivy Sign in Moyamoya Disease: A Comparative Study of the FLAIR Vascular Hyperintensity Sign Against Contrast-Enhanced MRI

Abstract: BACKGROUND AND PURPOSE: The ability of the ivy sign on contrast-enhanced T1-weighted MR imaging (CEMR) to reflect cerebral perfusion and postoperative revascularization in Moyamoya disease remains largely unknown. We aimed to compare the capabilities of CEMR and FLAIR. MATERIALS AND METHODS: CEMR, FLAIR, arterial spin-labeling, and DSA were performed in 44 patients with Moyamoya disease. The ivy sign was scored separately on CEMR and FLAIR using the Alberta Stroke Program Early CT Score. The status of leptomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Although our study with 11 cases showed PAO safety, we must be aware that the fate of the patients may not fundamentally change because in this study, most patients had late-Suzuki stage MMD (stages IV, V, and VI) ( Tables 1 , 2 ), the prognosis was worse, PAO for the aneurysm only can bring a moment of peace, and extracranial-intracranial bypass may be necessary to improve brain flow perfusion ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 80%
“…Although our study with 11 cases showed PAO safety, we must be aware that the fate of the patients may not fundamentally change because in this study, most patients had late-Suzuki stage MMD (stages IV, V, and VI) ( Tables 1 , 2 ), the prognosis was worse, PAO for the aneurysm only can bring a moment of peace, and extracranial-intracranial bypass may be necessary to improve brain flow perfusion ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 80%
“…The degree of proximal stenosis may not be the only determinant of disease severity if the compensation through collateral vessels is adequate. The "ivy sign" on FLAIR is a presentation of leptomeningeal collaterals and has been reported to be related to clinical severity and hemodynamics [10] . According to the semiquantitative analysis of the manifestation of the "ivy sign" in different Suzuki's stages and the comparisons with collaterals shown on DSA, we found that there were 10.00% regions in the early stage, 56.88% in the midstage and 28.00% in the late stage with the "ivy sign"; there were 14.17% regions in the early stage, 70.31% in the mid-stage and 35.00% in the late stage with leptomeningeal collaterals on DSA.…”
Section: Discussionmentioning
confidence: 99%
“…The ivy sign grade of each hemisphere was de ned as follows: 0 (absence), 1 (less than half of the cortical surface), and 2 (more than half of the cortical surface). Ivy sign severity was classi ed as mild (grade 0-1) or severe (grade 2) 8, 12 . Two neuroradiologists reviewed the ivy sign independently without knowledge of the clinical information or DSA/CTP ndings.…”
Section: Imaging Analysis Mri Analysismentioning
confidence: 99%
“…Conventionally, we utilized Suzuki's angiographic stage 12 to stand for the situation of cerebral morphology. Based on the literature, Suzuki's angiographic stage was graded into 6 stages,≥4 stages represent severe disease.…”
Section: Cerebral Morphology Assessmentmentioning
confidence: 99%
See 1 more Smart Citation